Willingness to reduce alcohol consumption predicted by short-form video exposure, media involvement, psychological bias, and cognitive factor - Chung, Donghwa; Meng, Yanfang (Frontiers in Psychology, 2024)
Introduction Through previous studies, Chinese college students are known to be prone to alcohol consumption, which can lead to health-risk behaviors such as high blood pressure, heart disease, stroke, liver disease, and digestive problems. However, little is known about how popular social media platforms (e.g., short-form video applications) can positively impact their willingness to reduce alcohol consumption. This study was guided by the theory of optimistic bias; we investigated the direct, mediated, and moderating effects of exposure to anti-alcohol consumption short-form videos and short-form video involvement on Chinese college students’ willingness to reduce their alcohol consumption. Methods The current study has an empirical cross-sectional design and employed an online survey from September 1st, 2022, to November 1st, 2022. The survey specifically targeted Chinese college students, who are the most common users of short-form video applications. The accumulated data underwent rigorous examination, including hierarchical regression, mediation, and moderation analyses, all conducted using the PROCESS macro 4.0 within SPSS version 22. Results A total of 434 participants, aged 18–24 years, were included in this study. There were mediating effects regarding Chinese college students’ exposure to anti-alcohol consumption short-form videos (β = 0.35, p < 0.01, 95% CI [0.17, 0.63]) and short-form video involvement (β = 0.44, p < 0.001, 95% CI [0.20, 0.65]) on their willingness to reduce alcohol consumption via reversed optimistic bias. Moreover, perceived prevention of heavy drinking control (β = 0.05, p < 0.001, 95% CI [0.01, 0.09]) played mediating roles in the relationship between exposure to anti-alcohol consumption short-form videos and willingness to reduce alcohol consumption. Conclusion This study is one of the earliest studies to examine the intricate effects of exposure to anti-alcohol consumption short-form videos and short-form video involvement on the willingness to reduce alcohol consumption among Chinese college students. In addition, this study confirms that regardless of whether Chinese college students are conscientious, exposure to anti-alcohol consumption short-form videos did not increase their level of reversed optimistic bias. The empirical findings of this study are critical and can provide practical insights for Chinese health departments that encourage Chinese college students to minimize alcohol consumption.